System Level Exergy Assessment of Strategies Deployed for Solid Oxide Fuel Cell Stack Temperature Regulation and Thermal Gradient Reduction - Tang, S.; Amiri, A.; Tadé, Moses (American Chemical Society, 2019)
© 2019 American Chemical Society. Several operational strategies for solid oxide fuel cell (SOFC) temperature regulation and temperature gradient minimization at cell scale have previously been assessed by the authors (Amiri et al., Ind. Eng. Chem. Res., 2016). The application of such strategies at system scale, however, requires a numerical linkage between the cell and the system performance metrics allowing simultaneous evaluation of the dominant process interactions. The objective of this study is to analytically examine the effectiveness and applicability of the mentioned thermal management methods at system scale. To achieve this, a system level exergy analysis is presented by using a modeling platform in which a detailed four-cell short stack module and the balance-of-plant (BoP) are integrated. Linkage between the system performance metrics and the stack internal temperature gradient is specifically emphasized. For this, the exergy intensive points (unit operations) are identified throughout the plant. Subsequently, the effective strategies that had been employed for the cell level thermal management proposed in our previous work (Amiri et al., Ind. Eng. Chem. Res., 2016) are examined at the system level capturing the effects on the state of BoP exergy intensive components. Moreover, fuel design is proposed and evaluated as a potential thermal management strategy. Combination of a variety of measures including the exergy destruction rates, the electrical and thermal efficiencies, and the stack internal temperature gradient provides a comprehensive set of data contributing to the SOFC system thermal management.